Bitcoin on Economic Growth (Case of 8 Asia Countries) - Titalessy, Pisi Bethania; Situmeang, Radian Januari (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2024)
In recent years, the price of Bitcoin has risen sharply on balance, despite some fluctuations. The latest price surge of the largest cryptocurrency prompted talk about Bitcoin's future. This research was conducted to confirm the impact of cryptocurrency which is Bitcoin on economic growth in Asian countries. Many studies have talked about cryptocurrencies on the technological side, but there are still few references to research that analyzes cryptocurrencies with economic growth. Using panel data regression, this study correlates cryptocurrencies, in this case, Bitcoin, as a type of cryptocurrency that is best known with GDP as a variable that represents economic growth. This study also has 4 other variables as control variables which will ensure the results are not biased. Namely the Internet (I), Capital (K), Labor (L), and Technology (T), as in Solow's growth theory which reviews growth through its supply side, the function of production inputs. This study took samples from 8 Asian countries with the most Bitcoin transactions (Japan, China, India, Singapore, Indonesia, Malaysia, Thailand, and Hongkong) from 2014 to 2020.